TRANSLANGUAGING PEDAGOGY IN A MULTILINGUAL PRIMARY CLASSROOM: EFFECTS ON COGNITIVE FLEXIBILITY AND ACADEMIC LITERACY - Andrei Popa; Natalia Ionescu; Ion Mih?ilescu (International Journal of Educatio Elementaria and Psychologia, 2025)
The increasing linguistic diversity in classrooms presents both challenges and opportunities for enhancing student learning. Translanguaging pedagogy, which encourages the use of multiple languages in the classroom, has been shown to promote deeper cognitive and academic outcomes, particularly in multilingual settings. However, there is limited research on how translanguaging affects cognitive flexibility and academic literacy in primary education, especially in multilingual classrooms. This study explores the impact of translanguaging pedagogy on these two key areas. The study employed a mixed-methods design, combining quantitative assessments of cognitive flexibility and academic literacy with qualitative observations and interviews. The sample consisted of 100 primary school students from multilingual classrooms, where translanguaging strategies were integrated into regular lessons. Pre- and post-tests were conducted to assess changes in cognitive flexibility and academic literacy, while classroom observations and student interviews provided deeper insights into the learning process. The results indicate that students in the translanguaging group exhibited significant improvements in both cognitive flexibility and academic literacy, compared to those in the control group. Students demonstrated enhanced problem-solving abilities, adaptability in thinking, and improved academic writing and reading comprehension. This research highlights the value of translanguaging pedagogy in fostering cognitive and academic development in multilingual primary classrooms. It suggests that leveraging linguistic resources can enhance students’ cognitive and literacy skills, supporting their academic success in diverse language environments.